Weighted Committee Games - Sascha Kurz; Alexander Mayer; Stefan Napel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Players in a committee, council, or electoral college often wield asymmetric numbers of votes. Binary decision environments are then conventionally modeled as weighted voting games. We introduce weighted committee games in order to describe decisions on three or more alternatives in similarly succinct fashion. We compare different voting weight configurations for plurality, Borda, Copeland, and antiplurality rule. The respective geometries and very different numbers of structurally non-equivalent committees have escaped notice so far. They determine voting equilibria, the distribution of power, and other aspects of collective choice.
Keywords: C71; D71; C63; 330; voting games; weighted voting; geometry of voting; voting power; Borda rule; Copeland rule; plurality; antiplurality